Knowledge, attitude, and experience of dentists toward child abuse and neglect. A cross-sectional study - Ankit Mahajan; Abhigyan Manas; Narita Jamwal; Jazib Nazeer; Noura Alessa; Akriti Agrawal; Jagadish P. Rajguru; Vaibhav T. Chougule; Delphine Rao (Journal of Family Medicine and Primary Care)
Context: Child abuse and neglect can be described as all kinds of physical, emotional, and sexual abuse, neglect, commercial and/or any other type of exploitation resulting in any potential of causing hurt or an actual form of harm to a child’s general health, growth, survival, and dignity. The dentist is in a position to identify physical signs of physical abuse in a child hence, it is important to gauge the knowledge level and perception regarding child abuse and neglect. Aim: The aim of the present study was to ascertain the knowledge, attitude, and experience regarding child abuse and neglect among dentists in India. Materials and Methods: This cross-sectional, descriptive, survey-based study was conducted on 100 dental practitioners all over India using a pre-validated questionnaire. The study was approved by the institutional ethics committee. Responses received were recorded in an Excel Worksheet and analyzed using descriptive statistics and Chi-square statistical tool using SPSS software (version 21.0). Results: We found that 85% of respondents reported child abuse cases of a physical and sexual nature and 87% had knowledge that law enforcement agencies are responsible for reporting such cases. Also, 56% believed that such cases could be reported using electronic mail while other sources were telephone, letters, or personal intervention. Only 12% were fearful of litigation and 24% were concerned about such exposure to a child. Conclusion: A total of 11% of dentists experienced barriers in reporting such cases while 17% reported with no barriers. Child abuse and neglect are often underreported due to various reasons. This survey has attempted to assess the knowledge, attitude, and experience about child abuse and neglect and has found a few prominent reasons for not reporting such incidents.